2017
DOI: 10.3390/ijerph15010040
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Internet Gaming Disorder: Psychological Factors and Internet Gaming Characteristics

Abstract: Background: Understanding the risk factors associated with Internet gaming disorder (IGD) is important to predict and diagnose the condition. The purpose of this study is to identify risk factors that predict IGD based on psychological factors and Internet gaming characteristics; Methods: Online surveys were conducted between 26 November and 26 December 2014. There were 3568 Korean Internet game users among a total of 5003 respondents. We identified 481 IGD gamers and 3087 normal Internet gamers, based on Diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 54 publications
6
99
1
6
Order By: Relevance
“…Some studies have also shown that individuals characterized by a propensity to act impulsively use the game as an escape from reality to get away from painful emotions that derive from distorted beliefs relating to self, others and the surrounding world (38,39). In our study it emerged that somatization, depression and sleep disturbances are predictive in online gambling addiction behaviors, according to some literature data (33,40,41).…”
Section: Discussionsupporting
confidence: 61%
“…Some studies have also shown that individuals characterized by a propensity to act impulsively use the game as an escape from reality to get away from painful emotions that derive from distorted beliefs relating to self, others and the surrounding world (38,39). In our study it emerged that somatization, depression and sleep disturbances are predictive in online gambling addiction behaviors, according to some literature data (33,40,41).…”
Section: Discussionsupporting
confidence: 61%
“…Regarding the geographic characteristics of the included studies, nine were from China (Ding et al 2014;Du et al 2016;Du et al 2017;Hu et al 2017;Tian et al 2018;Wang et al 2016Wang et al ,2017Wu et al 2018;Yao et al 2017), eight were from South Korea (Choi et al 2014;Hyun et al 2015;Kim et al 2017a;Kim et al 2017b;Lee et al 2017;Lee et al 2017;Rho et al 2017;Ryu et al 2018), three were from Germany (Rehbein et al 2010;Sariyska et al 2017;Walther et al 2012), two were from Australia (Bailey et al 2013;Metcalf and Pammer 2014), two were from Singapore (Gentile et al 2011;Liau et al 2015), two were from the USA (Bargeron and Hormes 2017; Stockdale and Coyne 2018), one was from Spain (Irles and Gomis 2016), one was from the UK (Irvine et al 2013), one was from Belgium (Deleuze et al 2017), one was from the Czech Republic (Blinka et al 2016), and one was from Taiwan (Yen et al 2017). Additionally, there were two cross-cultural studies.…”
Section: Country In Which the Data Were Collectedmentioning
confidence: 99%
“…Future studies should address both parents' representations of parenting style in order to gather more detailed and conclusive information, as well as other important family-related variables, such as household income, the presence of related parental addictions or mental health issues, which may impact the mental health of their offspring and their relationships. O ther important variables which future studies may consider are related to game-related factors such as gaming duration or game genre (Rho et al, 2017), the sense of presence (i.e., experiencing the gaming, virtual world as a real one; Stavropoulos, Burleigh, Beard, Gomez, & Griffiths, 2018), the use of an avatar and the bond created between the player and the avatar , and the cultural norms that might mediate addictive play patterns (Kuss, 2013;Snodgrass, Zhao, Lacy, Zhang, & Tate, 2019).…”
Section: Limitationsmentioning
confidence: 99%